HABLUMMINALLAH AND HABLUMMINANNAS OF ZAKAH - Muhammad Dandy Alif Wildana; Asfi Manzilati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study was conducted to understand the aspects that consist in zakah, as one out of five principles of islam : religious, economic, and social. Al Qur'an, as the holy book of islam, Prophet Muhammad (PBUH) hadiths, along with books and scientific journal are used as data. Literature review is used as the approach of this study. Zakah cannot be treated only as a form of worship towards Allah, The Creator of All, but zakah has further means and functions, and benefits to all humanity through its worldly aspects, namely economic and social. The correct establishment of zakat can be a solution on solving the problems that emerge in the economic and social areas. This research is limited on viewing the effects of zakah in the light of its benefit on religious, economic and social. The next research that conducted on this field perhaps can broaden the view and fill the empty space, because zakah still can be seen on another point of view or perspective. Any further research conducted on the theme of zakah will furthermore justify the position of it as a tool of community stability that affect not only for moslem as the follower of islam, but to all of humanity.Keywords : Islam, Zakah, Al Qur'an, Hadiths of Prophet Muhammad (PBUH), Economic, Social